PENERAPAN PSAK 72 TERKAIT PENDAPATAN DARI KONTRAK DENGAN PELANGGAN PADA PT TELEKOMUNIKASI INDONESIA TBK - Puspamurti, Hayati; Firmansyah, Amrie (School of Accountancy, University of Agung Podomoro, 2020)
This study aims to review the application of PSAK 72 regarding Revenue from Contracts withCustomers at PT Telkom Tbk. This study employs qualitative methods with a literature study approach,content analysis, and interviews. Interviews were conducted with two informants consisting ofacademic and PT Telkom internal party. It was conducted in May 2020. This study concluded thatPSAK 72 (2017) by PT Telkom Tbk was effective since January 1, 2020, and is not an earlyapplication in Indonesia because, in 2018 and 2019, PT Telkom Tbk used PSAK 23 (2014). Theimplementation of IFRS 15 (2014) by PT Telkom Tbk since 2018 has not made the financial reportssubmitted to the IDX early-adopting PSAK 72 (2017). PT Telkom Tbk has made preparations relatedto the implementation of PSAK 72 (2017) since the end of 2016.